Symptomatic cutaneous sparaganosis (tapeworm) in a child: A case report - Russell B. Hawkins; Michael Feely; David Saulino; Steven L. Raymond (Elsevier, 2024)
Introduction: Cutaneous sparganosis is a rare parasitic infection in the United States pediatric population. Case presentation: A 12-year-old female complained of persistent pain secondary to a subcutaneous nodule that had been present for approximately three months. On examination, an approximately 2.5 cm periumbilical subcutaneous mass was appreciated with severe tenderness to light palpation. She had no overlying skin changes or drainage from the area. Ultrasound findings were inconclusive for a diagnosis. MRI revealed a 2.5 x 0.8 × 1.9 cm serpiginous soft tissue lesion which was read as possible abdominal wall endometriosis. She reported worsened pain associated with the lesion during her menstrual cycle, but no significant size changes. After discussion with the patient and her family, she was taken for surgical excision of the skin lesion. During the operation, a long, narrow, tubular segment of white tissue was removed along with an associated granuloma cavity. Gross and microscopic examination demonstrated a cestode consistent with the Spirometra species (sparganosis). Postoperatively, the patient was treated with a three-day course of oral albendazole. Stool sample testing demonstrated no evidence of ova or parasites. She recovered without complications or known recurrence. Conclusion: Sparaganosis can present as a persistent painful subcutaneous nodule. This case underscores the need to consider excision of subcutaneous lesions with unusual symptoms.